ตัวประกอบสมรรถนะพยาบาลวิชาชีพ โรงพยาบาลชุมชน ภาคใต้ - ชลธิชา ชาญสวัสดิ์ (จุฬาลงกรณ์มหาวิทยาลัย, 2010)
The purpose of this research was to study the characteristics of professional nurses’ competencies in community hospitals, southern Thailand. The sample of 478 professional nurse form community hospitals, who had working experience of community nurses at least 5 years. The research instrument was the tested for content validity and reliability. The Cronbach’s Alpha coefficient was 0.98. The data were analyzed by using Principle Component Extraction and Orthogonal Rotation with Varimax Method. The research findings were as follows: There were 10 significant factors of competency of professional nurses in community hospitals, southern Thailand. These factors were described by 85 items that accounted for 65.555% of total variances. The factor named form exploratory factor analysis was: 1) Emergency and critical nursing described by 11 items, accounted for 9.635 % of the variance. 2) Management and leadership described by 17 items, accounted for 9.623 % of the variance. 3) Health promotion and prevention described by 10 items, accounted for 8.026 % of the variance. 4) Knowledge and ability in using the nursing process described by 6 items, accounted for 6.959 % of the variance. 5) Using technology and information described by 6 items, accounted for 6.650 % of the variance. 6) Communication and relationship described by 9 items, accounted for 6.028 % of the variance. 7) Nursing ethics described by 6 items, accounted for 5.736 % of the variance. 8) Transcultural nursing described by 7 items, accounted for 5.398 % of the variance. 9) Academic and research described by 6 items, accounted for 5.152 % of the variance. 10) Practice nursing in the Community described by 7 items, accounted for 4.130% of the variance.